Interdiffusion Behavior of Aluminide Coated Two-Phase Î±2-Ti3Al/Î³-TiAl Alloys at High Temperatures - Basuki, Eddy A.; Yuliansyah, Muhammad I.; Rahman, Farhan M.; Muhammad, Fadhli; Prajitno, Djoko (Journal of Engineering and Technological Sciences, 2016)
Lower density materials of TiAl based intermetallic alloys have recently attracted intensive attention for the replacement of nickel-based superalloys used at high temperatures. As aluminium-rich titanium aluminide intermetallic compounds are normally brittle, two-phase Î±2-Ti3Al/Î³-TiAl alloys have been developed. To increase the corrosion resistance of these alloy systems, an aluminide coating of TiAl3 layer is normally applied. During operation at high temperatures, however, interdiffusion between the coating and the alloy substrate can occur and decrease the TiAl3 layer thickness of the coating. The effects of temperature exposure on the growth of the TiAl2 interdiffusion zone layer on two-phase Î±2-Ti3Al/Î³-TiAl alloys with a chemical composition of Ti-47Al-2Nb-2Cr-0.5Y-0.5Zr are presented in this paper. The exponents for kinetics and rate constant of the TiAl2 interdiffusion layer growth of this multi-component system were found under variation of temperature. The results were compared with those from other researchers.